2019
DOI: 10.1093/cdn/nzz039.or33-07-19
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Pattern Score, Diet Quality, and Major Neurodegenerative Diseases: A Meta-analysis of Observational Cohort Studies (OR33-07-19)

Abstract: Objectives Diet is an important lifestyle factor that may prevent or slow the onset and progression of neurodegeneration. Recent studies suggest that adherence to a healthy dietary pattern is associated with reduced risk of cognitive decline. Few studies have examined the relationships between dietary patterns and risk of clinical neurodegenerative disease outcomes. In this meta-analysis, we examined the associations between overall dietary patterns, assessed a priori and a posteriori, and ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Calculated totals were used to categorize level of physical activity as poor, intermediate, or ideal based on time engaged in moderate and vigorous activity. Dietary scores were calculated based upon the total number of servings of fruit, vegetables, whole grains, sugar-sweetened beverages, and sodium intake over 24 h, as previously described [26] . NHANES reports each food item with a US Department of Agriculture food code and portion size [27] .…”
Section: Methodsmentioning
confidence: 99%
“…Calculated totals were used to categorize level of physical activity as poor, intermediate, or ideal based on time engaged in moderate and vigorous activity. Dietary scores were calculated based upon the total number of servings of fruit, vegetables, whole grains, sugar-sweetened beverages, and sodium intake over 24 h, as previously described [26] . NHANES reports each food item with a US Department of Agriculture food code and portion size [27] .…”
Section: Methodsmentioning
confidence: 99%
“…The knowledge about the benefits of exercise in humans is increasingly extensive. Beyond its well-known role as cardioprotective, scientific evidence has shown that exercise also enhances various brain functions, positioning it as a significant neuroprotector and therapeutic tool in the prevention of mental disorders and neurodegenerative diseases [43]. Especially in an increasingly aging population, physical exercise proves to be an effective tool in treating neurodegenerative pathology, while improving functional capacity, mobility, and autonomy in dementia patients [44].…”
Section: Interconnections Between Physical Activity and Neurodegenera...mentioning
confidence: 99%
“…In this context, the neuroprotection processes induced by physical activity are attributed to increased production of neurotransmitters and neurotrophic factors, as well as neural hormone production. Physical activity provides neuroprotection and neuroprevention by promoting better cognition, memory, sleep, angiogenesis in the nervous system, and reducing stress, anxiety, insulin resistance, and neuroinflammation [43]. Physical exercise, especially aerobic exercise, benefits synaptic plasticity, particularly in terms of learning, memory, and motor function.…”
Section: Interconnections Between Physical Activity and Neurodegenera...mentioning
confidence: 99%
“…An increasing number of diseases are being proven to be prevented by adopting specific dietary patterns, and this has also been indicated in meta-analyses on the risk of cardiovascular diseases, 4 chronic kidney disease, 5 cancers (eg, colorectal, 6 lung, 7 endometrial, 8 breast), 9 frailty, 10 neurodegenerative diseases, 11 and attention deficit-hyperactivity disorder, 12 among others. Moreover, specific dietary patterns have been attributed to a lower risk of cardiometabolic diseases 13 and preterm birth, 14 and a lower level of C-reactive protein.…”
Section: Introductionmentioning
confidence: 99%